Formulasi Dan Uji Aktivitas Antibakteri Sediaan Gel Ekstrak Etanol Daun Kerai Payung (Fillicium Decifiens) Terhadap Bakteri Propionibacterium acne dan Staphylococcus epidermis - Gadis Minanda Fauziah Purba; Idaman Lase; Reh Malem br Karo; Razoki Lubis; Finna Piska (Universitas Prima Indonesia, 2023)
Sunshade (Fillicium decipiens) is a member of the Sapindaceae family, including some active antibacterial substances. To determine the antibacterial activity of Fillicium decipiens leaf ethanol extract gel against Propionibacterium acne and Staphylococcus epidermis bacteria, this study produced Fillicium decipiens leaf ethanol extract gel preparations using various extract concentrations and other formulations. Fillicium decipiens leaf extraction method by maceration using 96% ethanol. Prepare Fillicium decipiens leaf ethanol extract gel formulation using carbopol 940 base using various concentrations of Fillicium decipiens leaf ethanol extract, each 5%, 10%, and 15%. Gel preparations were tested for the physical properties of the gel, including an organoleptic test, pH test, homogeneity test, and spreadability test. As a result of organoleptic tests, the ethanol extract gel preparation of Fillicium decipiens leaves in each formula, namely F0 (clear color, extract aroma, semi-solid), F1 (greenish-brown color, extract aroma, semi-solid), F2 (greenish-brown color, extract aroma, semi-solid), F3 (greenish brown in color, parasol extract, relatively viscous), for the homogeneity test of the gel preparation formula, it was obtained entirely homogeneous. The formulation that produced the highest inhibition against Propionibacterium acne and Staphylococcus epidermis bacteria was formulation 3 (15% concentration of Fillicium decipiens leaf extract), where the inhibition zone obtained was 17.99 mm for Propionibacterium acne and 17.45 mm for Staphylococcus epidermis.